The cosmo-biography of Sun Ra : the sound of joy is enlightening - Raschka, Christopher (Candlewick Press, 2014)
A one-hundredth birthday tribute to the late jazz artist explores his observations about humanity's discriminatory and violent behaviors as well as his efforts to forge world peace through music with the Sun Ra Arkestra.